Arthrogenic muscle inhibition after ACL reconstruction: a scoping review of the efficacy of interventions. Issue 5 (7th September 2018) - Sonnery-Cottet, Bertrand; Saithna, Adnan; Quelard, Benedicte; Daggett, Matt; Borade, Amrut; Ouanezar, Hervé; Thaunat, Mathieu; Blakeney, William G
Abstract : Objective: To determine whether reported therapeutic interventions for arthrogenic muscle inhibition (AMI) in patients with ACL injuries, following ACL reconstruction, or in laboratory studies of AMI, are effective in improving quadriceps activation failure when compared with standard therapy in control groups. Design: A scoping review of the efficacy of interventions was conducted in accordance with the methodological framework of Arksey and O'Malley and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Search terms included 'arthrogenic muscle inhibition', 'quadriceps activation following knee injuries', 'anterior cruciate' or 'knee' combined with 'quadriceps activation', 'quadriceps inhibition', 'corticomotor', 'arthrogenic', 'brain activation' and 'neuroplasticity'. Articles were evaluated for risk of bias using the PEDro (Physiotherapy Evidence Database) criteria. The overall quality of evidence for each intervention was assessed using Grading of Recommendations Assessment, Development and Evaluation (GRADE). Data sources: PubMed, EMBASE and Cumulative Index to Nursing and Allied Health Literature databases. Eligibility criteria for selecting studies: Isolated case reports and articles reporting outcomes in patients with chronic disease or major trauma were excluded. All other original research articles were included. Results: 780 potential articles were identified. 20 met the inclusion criteria. These studies provided a moderate quality of evidence to support the efficacy of cryotherapy and physical exercises in the management of AMI. There was low-quality evidence for efficacy of neuromuscular electrical stimulation and transcutaneous electrical nerve stimulation, and very low-quality evidence for efficacy of ultrasound and vibration. Conclusions: This scoping review demonstrated moderate-quality evidence for the efficacy of cryotherapy and physical exercises in improving quadriceps activation failure after ACL injury and reconstruction. These therapeutic modalities are therefore recommended in the management of AMI.